Linked system assessment to support sustainable energy supplies “LiSA” - Rixrath, Doris; Schauer, Raphael; Sabo, Elena; Piringer, Gerhard (International Conference “Environmental Engineering”, 2023)
The globally agreed climate targets require an expansion of renewable energies within the entire supply system. To support this a well-developed set of methods is needed to assess technical, environmental, social, and economic impacts. These methods must cover the entire life cycle and should enable an efficient and target-oriented assessment of energy technologies and systems. The Josef-Ressel (JR) centre LiSA (established 1st January 2022) will address this need. It will develop assessment methods focusing on thermal energy conversion systems embedded in a renewables-rich energy landscape.
Keywords: environmental life cycle assessment (LCA); social life cycle assessment (SLCA); life cycle costs (LCC); life cycle sustainability assessment (LCSA); sustainable energy supply